Association Between Smoking and Hypertension as Health Burden in Sidoarjo: A Case-Control Study - Muhammad Farid Dimjati Lusno (Hasanuddin University, 2020)
Noncommunicable diseases (NCDs) became major caused of premature death and health burden which rising disproportionately among low-income and lower-middle-income countries. There are common modifiable behavioral risk factors include tobacco smoking. In Indonesia there were 147.510 Cardiovascular (CVD) death caused by tobacco use which is 26% of all CVD deaths each year. The link between smoking and hypertension is still far to be completely identified. This study aim to analyze the relationship of smoking to hypertension. The study conducted with case control approach. The sampling method use probability sampling with the samples 172 respondent consist of 76 cases and 76 control. Hypertension patient data is obtained based on secondary data that has been owned by the Puskesmas.The findings showed that smoking (p=0,01, OR=3,1), early age of smoking (p=0,00, OR=6,5) with starting 6 – 19 years old higher OR then 20-33 years old (p=0,00,OR=4), duration of smoking (p=0,00, OR=9,9) in a group with 30 – 53 years of smoking higher than whose 9 – 29 years of smoking (p=0,0, OR=8,2), and type of cigarettes (p=0,001, OR=3,4). Smoking has association to hypertension as the modifiable factor which needs concerned from decision maker especially to linkage the program of NCDs especially in preventing hypertension.